Impact of lobular versus ductal histology on overall survival in metastatic breast cancer: a French retrospective multicentre cohort study. (March 2022) - Dalenc, Florence; Lusque, Amélie; De La Motte Rouge, Thibault; Pistilli, Barbara; Brain, Etienne; Pasquier, David; Debled, Marc; Thery, Jean-Christophe; Gonçalves, Anthony; Desmoulins, Isabelle; Levy, Christelle; Uwer, Lionel; et al.
Abstract: Background: The impact of the histological lobular subtype on overall survival (OS) in metastatic breast cancer (MBC) is still under debate, with very few data available. Patients and methods: Using the French national multicentre Epidemiological Strategy and Medico Economics [ESME]) data platform, the primary objective was to compare the OS of patients with invasive lobular carcinoma (ILC) versus invasive ductal carcinoma (IDC) MBC, with adjustment on the main prognostic factors using two approaches: multivariable analysis and matching with a propensity score. Secondary objectives were to compare first-line progression-free survival (PFS1) and describe patients and tumour characteristics. Results: Of the 16, 703 patients with MBC in the ESME database, 13, 111 met all inclusion criteria for the present analysis. One-thousand eight-hundred and four (13.8%) patients had ILC and 11.307 (86.2%) IDC. In the multivariable analysis, patients with ILC had a worse OS [hazard ratio (HR): 1.31; 95%CI 1.20–1.42; p < 0.0001] and a worse PFS1 (HR: 1.15; 95%CI 1.07–1.22; p < 0.0001) as compared with those with IDC, independently of hormone receptor and HER2 status. Interestingly, OS was better (HR 0.79; 95% confidence interval [CI] 0.64–0.98; p = 0.0302), worse (HR: 1.17; 95%CI 1.08–1.27; p = 0.0001) or similar (HR: 0.88; 95%CI 0.67–1.15; p = 0.3455) in patients with ILC with triple-negative, hormone receptor-positive/HER2-negative and HER2-positive MBC, respectively, compared with patients with IDC. Conclusion: Lobular histology is an independent adverse prognostic factor among women with MBC. ILC MBC could be considered a specific entity. Dedicated prospective studies are needed to tailor the management of these patients. Highlights: Invasive lobular metastatic breast cancer has a worse overall survival. They have a worse first-line progression-free survival than ductal carcinomas. Invasive lobular metastatic breast cancer should be considered a specific entity. Dedicated prospective studies are needed to tailor the management of these patients.